Reliability quantification and visualization for electric microgrids - Panwar, Mayank, author; Suryanarayanan, Siddharth, advisor; Zimmerle, Daniel, committee member; Yang, Liuqing, committee member (Colorado State University. Libraries, 2012)
The electric grid in the United States is undergoing modernization from the state of an aging infrastructure of the past to a more robust and reliable power system of the future. The primary efforts in this direction have come from the federal government through the American Recovery and Reinvestment Act of 2009 (Recovery Act). This has provided the U.S. Department of Energy (DOE) with $4.5 billion to develop and implement programs through DOE's Office of Electricity Delivery and Energy Reliability (OE) over the a period of 5 years (2008-2012). This was initially a part of Title XIII of the Energy Independence and Security Act of 2007 (EISA) which was later modified by Recovery Act. As a part of DOE's Smart Grid Programs, Smart Grid Investment Grants (SGIG), and Smart Grid Demonstration Projects (SGDP) were developed as two of the largest programs with federal grants of $3.4 billion and $600 million respectively. The Renewable and Distributed Systems Integration (RDSI) demonstration projects were launched in 2008 with the aim of reducing peak electricity demand by 15 percent at distribution feeders. Nine such projects were competitively selected located around the nation. The City of Fort Collins in co-operative partnership with other federal and commercial entities was identified to research, develop and demonstrate a 3.5MW integrated mix of heterogeneous distributed energy resources (DER) to reduce peak load on two feeders by 20-30 percent. This project was called FortZED RDSI and provided an opportunity to demonstrate integrated operation of group of assets including demand response (DR), as a single controllable entity which is often called a microgrid. As per IEEE Standard 1547.4-2011 (IEEE Guide for Design, Operation, and Integration of Distributed Resource Island Systems with Electric Power Systems), a microgrid can be defined as an electric power system which has following characteristics: (1) DR and load are present, (2) has the ability to disconnect from and parallel with the area Electric Power Systems (EPS), (3) includes the local EPS and may include portions of the area EPS, and (4) is intentionally planned. A more reliable electric power grid requires microgrids to operate in tandem with the EPS. The reliability can be quantified through various metrics for performance measure. This is done through North American Electric Reliability Corporation (NERC) metrics in North America. The microgrid differs significantly from the traditional EPS, especially at asset level due to heterogeneity in assets. Thus, the performance cannot be quantified by the same metrics as used for EPS. Some of the NERC metrics are calculated and interpreted in this work to quantify performance for a single asset and group of assets in a microgrid. Two more metrics are introduced for system level performance quantification. The next step is a better representation of the large amount of data generated by the microgrid. Visualization is one such form of representation which is explored in detail and a graphical user interface (GUI) is developed as a deliverable tool to the operator for informative decision making and planning. Electronic appendices-I and II contain data and MATLAB© program codes for analysis and visualization for this work.
Keywords: data analysis; electric power system; microgrid; reliability; smartgrid; visualization